Mathematical Modeling of Discharge Plasma Generation and Diffusion Saturation of Metals and Alloys; Advances in Computer Science Research; Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016) - Nguyen Bao Khyng (2016, 2016)
Title screen